Pengembangan Perangkat Pembelajaran IPA Berbasis Model Pembelajaran Inkuiri Pada Materi Sistem Pencernaan Untuk Melatih Keterampilan Proses Siswa Smp Kelas VIII Dan Meningkatkan Hasil Belajar Siswa - journal journal; Idzi’ Layyinati (Jurnal Pendidikan Islam, 2019)
Abstract: This research has purpose to produces learning materials that proper theoritically and empirically that consists of lesson plan, student work sheet, student book on digestive system that supported by increasing of student achievementand student responses towards learning that try process skils with junior high school research subject in Sidoarjo. This research used 4D development model but this research did not use dissiminate with one group pretes posttest in try out. Data collecting method, questionnaire, test and observation. Data analysis used qualitative descriptive technic. Research findings showed that validation of learning materials, namely syllabus, lesson plan, student book, and student worksheet was 82.5%, 91.3%, 80.3%, 85.0%; respectively lesson plan implementation was high and students response very positive (80.3). Learning materials that developed was proper to be used in learning and increased student achievement.